Histological Comparison of Effectiveness of Low Doses of Doxycyclineand Atorvastatin on gingival Inflammation and Alveolar Bone Loss in Experimental Model of Periodontitis in Rats - Masoumi, Sara; Andisheh-tadbir, Azadeh; Firozabadi, Negar; Bahmanpour, Maryam; Tanideh, Nader (Journal of Dental School, 2019)
Objectives: The purpose of this study was to evaluate the effect of low dose doxycycline and atorvastatin on gingival inflammation and alveolar bone loss in an experimental model of periodontitis in rats. Methods: Forty male Sprague Dawley rats were divided into four study groups as follows: (I) experimental periodontitis control, (II) rats with periodontitis treated with low dose atorvastatin (10 mg/kg), (III) rats with periodontitis treated with low dose doxycycline (6 mg/kg) and rats with periodontitis treated with both doxycycline and atorvastatin. Periodontitis was induced by ligature placement around the upper left second molar foe seven days. The periodontitis group received saline, periodontitis/doxycycline group received doxycycline by oral gavage, periodontitis/atorvastatin group received atorvastatin by oral gavage and doxycycline/atorvastatin group received both drugs simultaneously (6 and 10 mg/kg, respectively) for 21 days after ligature placement. Then, the rats were sacrificed and their maxillae were removed, defleshed, and prepared for histopathological examination. Data were analyzed statistically by the Kruskal-Wallis test and Mann-Whitney U test at 5% level of significance and presented as frequency Results: Using a combination of doxycycline and atorvastatin caused a significant decrease in gingival inflammation and alveolar bone loss (16.5%) and collagen degradation (13%) when compared to the control group (36.10% and 36.95%, respectively; P<0.001). Conclusion: Low dose atorvastatin and low dose doxycycline synergically prevented alveolar bone loss and collagen degradation in ligature-induced periodontitis in rats.